PROFETHIC CHARACTER SCALE SEBAGAI INSTRUMEN FEET AND PROPER TEST - A. Said Hasan Basri, S.Psi., M.Si. (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
The phenomenon of measuring a person's capacity and capability, even his characteristics and temperament, is extremely difficult. Need an instrument to measure it. Therefore, how many leaders who look capable, polite and commendable. But instead he did an anti-climax with acts of corruption, or other bad things, when he was already a leader. This study aims to compile and develop a measuring instrument Profetic Character Scale as a fit and proper test instrument. Then describe it quantitatively. The method used in this research is empirical method. The approach used is quantitative descriptive to describe the construction of a psychological measuring instrument by looking at the psychometric properties of the preparation and development of the Profethic Character Scale measuring instrument. The samples involved were 228 people taken purposively. The data collection was carried out online and offline with members of the PABKI organization (Indonesian Islamic Counseling Guidance Experts Association). The hypothesis proposed was that the Profethic Character Scale as a Feet and Proper Test instrument has a high level of validity and reliability. The results of the validity analysis shown in the item correlation (rix) valid items on the Profethic Character Scale as the Feet and Proper Test instrument move from 0.400 to 0.743, as well as the results of the reliability test the score moves from the lowest of 0.926 to the highest its Alpha Cronbach value is 0.929. Based on the effective value of each dimension, Shiddiq has 0.874, Fathonah has 0.879, Amanah has 0.898, and Tabliq has 0.860. The highest amount of effective contribution is obtained by the Amanah dimension, which is 0.898. the four dimensions have a very high effective contribution to the Profethic Character Scale as a Feet and Proper Test instrument. Based on the results of factor analysis starting from extraction with correlation matrix analysis, on four dimensions with total initial eigenvalues, the results of factor analysis using the Kaiser-Meyer-Olkin Measure of Sampling Adequacy and Bartlett's Test of Sphericity KMO and Bartlett's Test obtained KMO values or scores, even the results anti-image correlation analysis, the correlation value of the dimensions is very high, this proves that the Profethic Character Scale as a Feet and Proper Test instrument has a high degree of correlation with its dimensions.